POLICY MODEL FOR THE PROTECTION OF INDONESIAN MIGRANT WORKERS' REMITTANCES BASED ON PANCASILA: A COMPARATIVE ANALYSIS OF PROTECTION MECHANISMS AND SOCIAL JUSTICE VALUES BETWEEN INDONESIA AND THE PHILIPPINES - Lezhna Nayla Nurjihan; Utami Julianti (Awang Long Law Review, 2025)
Remittances from Indonesian migrant workers significantly contribute to national economic growth while serving as a crucial source of household welfare for their families. However, current remittance governance still faces regulatory and administrative challenges that hinder the full realization of economic benefits for migrant workers. This study aims to analyze Indonesia’s remittance protection policies through the lens of administrative law and international law while formulating an ideal policy model grounded in Pancasila values. This research employs a normative legal methodology using statutory, conceptual, and comparative approaches, particularly contrasting Indonesia’s policies with those of the Philippines. The findings reveal that although Indonesia has established a regulatory foundation through Law No. 18 of 2017 and national financial regulations, the implementation remains insufficient in addressing high transaction costs, limited access to formal financial services, and the widespread reliance on informal channels prone to fraud and loss of funds. Compared to the Philippines, Indonesia lags behind in ensuring interoperable cross-border payment systems, cost transparency, and financial literacy support for migrant workers and their families. Furthermore, weaknesses in regulatory oversight and interagency coordination contribute to unrecorded remittances and inadequate legal protection, especially for undocumented migrants. By adopting the social justice principles of Pancasila as a normative foundation, remittance policies should prioritize cost efficiency, accessible digital financial services, and strengthened supervisory mechanisms across institutions. Therefore, comprehensive government intervention is required to ensure that remittances operate not only as financial transfers but as instruments of equitable welfare and sustainable national development.